Endovascular approach in chronic aortoiliac disease in patient undergoing coronary artery bypass surgery - Fotini Ampatzidou; Charilaos-Panagiotis Koutsogiannidis; Aggelos Megalopoulos; George Trelopoulos; George Drossos (Annals of Cardiac Anaesthesia, 2019)
Internal thoracic artery (ITA) is an excellent conduit for coronary artery bypass surgery (CABG). We present a patient with known preoperative aortoiliac disease with anterior collateral pathway who had an indication for elective coronary bypass. The use of ITA in these patients may cause lower limb ischemia. Detecting Winslow's anastomotic pathway before CABG is of utmost importance.